Target detection methods based on UAV payloads - GUAN Donglin, ZHANG Jianting, WANG Yi, TAN Shuncheng (Zhihui kongzhi yu fangzhen)
Currently, unmanned intelligence is widely used in various fields, and unmanned automatic perception and monitoring related technologies are rapidly developing, opening up a new perspective for military reconnaissance and civilian monitoring. Starting from the perspective of sensor application, this article presents the current research achievements of motion target detection based on unmanned aerial vehicle (UAV) payloads, and discusses the trends of future technological development. Firstly, a common method for UAVs target detection is outlined. Then, the progress of UAVs in infrared, optical, and video synthetic aperture radar (SAR) target detection is highlighted, and the advantages and limitations of related technologies were revealed. Finally, future research directions such as developing cross-modal object detection technology, constructing intelligent detection systems, and enhancing the capability of super large models and so on are discussed, which are expected to provide reference and guidance for subsequent research.